The Influence of Population Number and Unemployment Rate on Poverty Level in North Tapanuli Regency 2013-2023 - Sheryl Valencia Pangaribuan; Riris Hotma Roito Manalu; Mika Jun Fera Br. Limbong; Elisabeth Fitryany Manik (Outline Journal of Economic Studies, 2026)
Purpose: This study aims to analyze the effect of population size and unemployment rate on poverty levels in North Tapanuli Regency during the period 2013–2023. The research is conducted to understand how demographic and economic factors contribute to poverty dynamics in the region. Methods: This study employs a quantitative approach using descriptive analysis and multiple linear regression methods. Secondary data were obtained from the Central Statistics Agency and processed using SPSS software. The analysis includes classical assumption tests, namely normality and multicollinearity tests, as well as hypothesis testing through partial (t-test) and simultaneous (F-test) analysis. Results: The partial test results reveal that population has a significant negative effect on poverty levels (t = -5.585; sig = 0.001), while unemployment does not have a significant effect (t = 0.880; sig = 0.408). The simultaneous test indicates that population and unemployment jointly have a significant effect on poverty levels (F = 17.175; sig = 0.002). The coefficient of determination (R²) shows that 83.1% of the variation in poverty levels can be explained by the two independent variables. Originality: This study provides empirical evidence on the relationship between population, unemployment, and poverty at the regional level, particularly in North Tapanuli Regency. It highlights that population dynamics play a more dominant role in influencing poverty compared to unemployment, offering insights for policymakers in designing targeted poverty alleviation strategies.